Врахування можливості інверсних потоків теплоти під час термічної обробки харчових продуктів - Федоров, Володимир Гаврилович; Кепко, Олег Ігорович; Скарбовійчук, Олександр Михайлович (My University, 2015)
Експериментально встановлено, що під час охолодження харчових продуктів за допомогою компресійної холодильної машини або нагрівання варених ковбас осцилюючим інфрачервоним випромінюванням з метою стабілізації поверхневого шару, виникають зворотні баластні теплові потоки (до 30 % від корисної теплоти). Наведено рекомендації щодо зменшення втрат теплової енергії. Result of direct measurement of heat flux with heat meter, which was mounted at the top center surface of the piece of a green cheese is unexpected: near 30 % of the heat which is released in the cheese and discharging with the cooling air is returned to the cheese. Return of heat to cheese is a ballast load for the chiller of ripening cheese chamber. Its elimination or minimization is a source of energy and resources saving. Ballast heat fluxes can occur in the heat treatment of food products, for example, during stabilization of the surface layer of cooked sausages with oscillating infrared roasting. Inversion heat flow occurs when the heat meter is on the opposite side (in shadow) of the transmitter. The selection of the coagulation time and the voltage on the emitter managed to reduce ballast heat flux in the central layers to one- third and the inverse flow of these layers - to zero. The maximum heat flux (and with it the total energy consumption) is reduced by 15—20 %.
Keywords: тепловий потік; тепломір; холодильне або теплове оброблення; heat meter; ballast heat flux; thermal treatment